The Lay Preacher Il laburismo di Tony Blair - Ravasio, Alessandro (Premio Cesare Alfieri «Cum Laude», 2023)
The volume aims to investigate Tony Blair's political figure, seeking to identify the elements of continuity and disruption between the blairian politics, the Labour Party's culture and history and Margaret Thatcher's political legacy. Several aspects of the British Prime Minister are examined: his biography, his rise in the party, his political ideas, his communicative style, and the choices he made once in power, both in domestic and foreign policy, especially in his relationship with the United States and the European Union. In particular, the volume focuses on the first six years of New Labour governments: from the landslide victory in 1997 to the declaration of war on Iraq in 2003, a decisive turning point in Blair's career and legacy.